2015
DOI: 10.1111/eip.12234
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient treatment has no impact on the core thoughts and perceptions in adolescents with anorexia nervosa

Abstract: Inpatient treatment of anorexia nervosa in adolescents does not significantly modify core anorexic thoughts and perceptions. This may explain the high relapse rates. Changes in core beliefs may be crucial for recovery and prevention of relapse in anorexia nervosa at this critical age. This study may have clinical implications for the development of better treatment strategies to target the gap between disturbed thoughts and distorted perceptions - the core aspects of anorexia nervosa and physical recovery duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
5
28
0
1
Order By: Relevance
“…These findings are in line with a recent study in adolescent AN inpatients (Fennig, Brunstein Klomek, Shahar, Sarel-Michnik, & Hadas, 2017) in which improvement in BMI during inpatient treatment was correlated with improvement in restraint and eating concern, but not in body dissatisfaction and weight/shape concerns. Moreover, at discharge from inpatient treatment, when achieving recovery of weight and stabilization of disordered eating, the suicidal ideation of these patients actually increased (Fennig et al, 2017). Similarly, adult ED patients have shown a correlation between suicidal ideation and preoccupation with weight and shape (Milos, Spindler, Hepp, & Schnyder, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in line with a recent study in adolescent AN inpatients (Fennig, Brunstein Klomek, Shahar, Sarel-Michnik, & Hadas, 2017) in which improvement in BMI during inpatient treatment was correlated with improvement in restraint and eating concern, but not in body dissatisfaction and weight/shape concerns. Moreover, at discharge from inpatient treatment, when achieving recovery of weight and stabilization of disordered eating, the suicidal ideation of these patients actually increased (Fennig et al, 2017). Similarly, adult ED patients have shown a correlation between suicidal ideation and preoccupation with weight and shape (Milos, Spindler, Hepp, & Schnyder, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with other previous studies in which no significant improvement was obtained after weight recovery in adolescents with AN. 12,37 However, Iniesta Sepúlveda et al 10 observed a decrease in core pathological features, while Hatch et al 11 obtained improvements in only two of the five psychopathological variables. Several studies have reported the existing gap between physical recovery and psychological change since they did not find significant associations between them, 12,34 which could explain the high rate of relapse of AN after discharge from inpatient units.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies found an improvement in general psychopathology, 10,11 while others did not find changes despite weight recovery. 12 Likewise, research on the efficacy and impact of interventions for AN should include evaluation of body image disturbance, in addition to changes in weight and medical stability. 13 An increase in physical activity (PA) can be considered a significant factor for the onset and maintenance of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…In understanding this behaviour, it is necessary to acknowledge that consumers with AN experience internal turmoil and distress from weight gain throughout hospitalization (Fennig et al . ). Nurses then experience challenges when delivering care that is not necessarily agreed to by the consumer.…”
Section: Introductionmentioning
confidence: 97%